Targeting Bone Cells During Sexual Maturation Reveals Sexually Dimorphic Regulation of Endochondral Ossification - Fairfield, Heather (JBMR Plus, 2020)
In endochondral ossification, chondroblasts become embedded in their matrix and become chondrocytes, which are mature cells that continue to proliferate, eventually becoming hypertrophic. Hypertrophic chondrocytes produce cartilage that is then resorbed by osteoclasts prior to bone matrix replacement via osteoblasts. Although sexually dimorphic bone phenotypes have long been characterized, specific modulation of the growth plate during a critical window in sexual maturation has not been evaluated. Here we report that specific depletion of osteocalcin‐ (OCN‐) expressing cells in vivo during sexual maturation leads to dimorphic bone phenotypes in males and females. At 6 to 8 weeks of age, OCN‐Cre;iDTR (inducible diphtheria toxin receptor‐expressing) mice were treated with diphtheria toxin (DT) for 2 weeks to deplete OCN+ cells. At the end of the study, long bones were collected for μCT and histomorphometry, and serum was collected for proteomic and lipidomic analyses. Ablation of OCN+ cells in mice leads to consistent trends for weight loss after 2 weeks of treatment. Females exhibited decreased skeletal parameters in response to OCN+ cell ablation treatment, as expected. However, OCN+ cell ablation in males uniquely displayed an expansion of hypertrophic chondrocytes, a widening of the growth plate, and an abnormal “clubbing” anatomy of the distal femur. Following DT treatment, mice from both sexes also underwent metabolic cage analysis, in which both sexes exhibited decreased energy expenditure. We conclude that skewing endochondral bone formation during longitudinal growth has a profound effect on body weight and energy expenditure with sex‐specific effects on developing bone. © 2020 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.